1994
DOI: 10.1037/0278-7393.20.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Role of attention in face encoding.

Abstract: Subjects studied faces in a full-or a divided-attention condition and then received a recognition test that included old faces, new faces constructed by combining facial features from previously studied faces ("conjunction faces"), and partly or completely new faces. Full-but not dividedattention subjects responded "old" more often to old than to conjunction faces; all subjects responded "old" to these faces more often than to partially or completely new faces. Thus it is less attentionally demanding to encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 36 publications
5
64
0
1
Order By: Relevance
“…In fact, our experiment indicates that face recognition is generally more accurate when responses are based on features rather than on familiarity. Other experiments have similarly indicated important roles of facial features in face recognition (e.g., Megreya & Burton, 2006;Reinitz, Morrissey, & Demb, 1994); our results are consistent with their findings. Finally, it is important to note that we did not specifically ask subjects which features they recognized.…”
Section: Implications For Theories Of Face Recognitionsupporting
confidence: 93%
“…In fact, our experiment indicates that face recognition is generally more accurate when responses are based on features rather than on familiarity. Other experiments have similarly indicated important roles of facial features in face recognition (e.g., Megreya & Burton, 2006;Reinitz, Morrissey, & Demb, 1994); our results are consistent with their findings. Finally, it is important to note that we did not specifically ask subjects which features they recognized.…”
Section: Implications For Theories Of Face Recognitionsupporting
confidence: 93%
“…Recognition of the old faces was greater than recognition of the conjunction faces, which in turn was higher than recognition of the feature faces, which itself was slightly greater than recognition of the new faces. These findings were interpreted as supporting the hypothesis that featural and configural information are coded independently, and that configural information requires greater attention than featural information does (e.g., Reinitz, Morrissey, & Demb, 1994). Further studies showed that inversion impairs the old face/conjunction face distinction, because these types of faces are distinguished not by the features that appear in the first stage of the experiment, but by the configuralholistic relations (e.g., Bartlett et al, 2003;McKone & Peh, 2006).…”
Section: A Holistic or Differential Effectmentioning
confidence: 65%
“…We can thus ask whether we form bound memory representation out of perceptually distinct features. This is a different approach than that taken in the existing literature on holistic representations of real-world objects; for example, some evidence suggests that faces are represented holistically as integral units rather than as bound but ultimately independent features of eyes, noses, and mouths (e.g., Tanaka & Farah, 1993; although see Reinitz, Morrissey, & Demb, 1994, for evidence that holistic face encoding is may depend on attention at encoding).…”
Section: Binding and Perceptual Integralitymentioning
confidence: 99%